In memoriam: Franco M Muggia - Pothuri, Bhavana; Curtin, John P (International journal of gynecological cancer, 2022)
It is with great sadness that we share news of the passing of Dr Franco M Muggia. He was a humble, gentle man, and yet a giant in our field. Dr Muggia was instrumental in bringing platinum based agents, pegylated liposomal doxorubicin, and other practice changing treatments into gynecologic oncology care. Dr Muggia always made time for anyone who asked for his wisdom and expertise. He was an amazing mentor, and his legacy will live on in the many trainees and colleagues he mentored throughout his prolific career. There are no words to describe the impact of his immense contributions to oncology and the effect he has had on the lives of so many trainees, colleagues and patients.